Infusing disability equity within rehabilitation education and practice: A qualitative study of lived experiences of ableism, allyship, and healthcare partnership - Feldner, Heather A.; Evans, Heather D.; Chamblin, Katherine; Ellis, Lesley M.; Harniss, Mark K.; Lee, Danbi; Woiak, Joanne (Frontiers in Rehabilitation Sciences, 2022)
Background: Addressing issues of diversity, equity, and inclusion (DEI) have become central in implementing inclusive and socially responsible rehabilitation education and clinical practice. Yet, constructs of disability and d/Deaf identity, culture, ableism, and allyship are often overlooked, or approached from outdated philosophical approaches that pathologize disability and fail to prioritize the lived experiences, expertise, intersectionality, and self-identified needs of people with disabilities. A Critical Disability Studies (CDS) framework may provide a background for better understanding and responding to these issues through allyship. Purpose: This study employed a CDS framework to understand the lived experiences of ableism and allyship from faculty, staff, and students on University of Washington (UW) campuses who identify as d/Deaf, disabled/with a disability, or as having a chronic health condition. Methods: During 2020-2021, we conducted in-depth, semi-structured interviews and focus groups with 22 diverse undergraduate and graduate students, faculty, and staff, one third who identified as people of color. Encounters were audio-recorded, transcribed verbatim, and coded using constant comparison until themes emerged. Results: Major themes that emerged from the data included (1) Ever-present ableism in healthcare, (2) Ableism at the intersections, (3) COVID: Surfacing ableism and expanding access, and (4) Disability allyship & healthcare partnership building. Experiences of ableism and allyship were identified at individual, group/unit, and institutional/systemic levels, though participants reported significantly fewer instances of allyship compared to experiences of ableism. Participants identified intersections between disability and other marginalized identities and juxtaposed the benefits of widespread adoption of access-increasing practices and technologies due to the COVID-19 pandemic, while also highlighting ways in which the pandemic created new inclusion obstacles. Conclusions: These data provide insights into ways of implementing inclusive practices in rehabilitation education, practice, and beyond. Rehabilitation students, faculty, and staff may not be aware of how ableism affects their disabled peers or underpins their professional education. It is important to cultivate opportunities within professional education and clinical training to explicitly address our collective role in creating inclusive and accessible academic and healthcare experiences for our diverse community post COVID-19. Using a Critical Disability Studies framework is a feasible and appropriate approach to address these opportunities.